1994
DOI: 10.1029/94ja00675
|View full text |Cite
|
Sign up to set email alerts
|

A Giotto/cometary dust interaction event near the diamagnetic cavity boundary

Abstract: A new scenario is suggested in order to explain the burst of particles observed by Giotto near the Halley ionopause. According to this scenario, an impact of a cometary dust particle against the Giotto spacecraft (identified by Neubauer et al. (1990)) creates a gas/plasma cloud. Cold cometary ions with a velocity of 70 km/s that impinge on the cloud around the spacecraft are scattered by the secondary ions/neutral species in the cloud. This scattering is shown to allow the cometary ions to enter the angular de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…They are generally consistent with dust impact events derived from spacecraft attitude perturbations by the Giotto camera [Curdt and Keller, 1990]. Whereas the plasma effects of one of these dust impacts were discussed in a previous paper/Israelerich and Ershkovich, 1994], this extended analysis focuses on the magnetic effects of the same event.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…They are generally consistent with dust impact events derived from spacecraft attitude perturbations by the Giotto camera [Curdt and Keller, 1990]. Whereas the plasma effects of one of these dust impacts were discussed in a previous paper/Israelerich and Ershkovich, 1994], this extended analysis focuses on the magnetic effects of the same event.…”
Section: Introductionsupporting
confidence: 74%
“…So the burst of ion fluxes may be explained either by a presence of suprathermal ions during the event, as was suggested by Goldstein et al [1989], or as a result of dust particle impact. We proposed that cometary ions, observed by the angle analyzers, were scattered by secondary ions and neutral atoms of the cloud [Israelevich and Ershkovich, 1994]. The angular distribution of the ions corresponded to the Rutherford formula for scattering, and it was shown that for scattering angles under consideration (and hence for corresponding impact parameters) there was no substantial difference between scattering by ions and by neutral atoms.…”
Section: Magnetic Field Disturbancementioning
confidence: 99%
See 1 more Smart Citation